Examining elementary preservice teachers’ self-efficacy and satisfaction in online teaching during virtual field experience - Sandra Baroudi; Zeina Hojeij; Lawrence Meda; Jacqui Lottin (Cogent Education, 2022)
The global pandemic of COVID-19 has forced many learning institutions to close or switch to remote learning as a preventative measure to reduce the spread of the virus. The greatest challenge was with practical courses where preservice teachers had to promptly acquire technological skills and online teaching pedagogies as part of their virtual field experience. This need for learning and applying online pedagogies and technological competencies to increase student performance can lead to different perceptions of self-efficacy in online teaching. The purpose of this study is to examine the predictors for enhancing preservice teachers’ self-efficacy and satisfaction in online teaching and to investigate the association of their self-efficacy beliefs and their satisfaction with online teaching. Elementary preservice teachers (n = 257) from two teacher preparation programs in two universities in the United Arab Emirates completed a 5-point Likert scale survey. Results revealed that participants reported a high level of self-efficacy and satisfaction in online teaching mainly regarding their abilities to engage students in online classrooms and use of computers/educational technology. Students’ technological knowledge was strongly correlated with participants self-efficacy beliefs. Interestingly, results showed that preservice teachers who have beginner experience in teaching scored significantly higher on their self-efficacy than those with moderate and advanced experience.